Stricter blood pressure control is associated with lower left ventricular mass in children after kidney transplantation: a longitudinal analysis of the 4C-T study - Sugianto, Rizky; Grabitz, Carl; Bayazit, Aysun; Duzova, Ali; Thurn-Valsassina, Daniela; Memaran, Nima; Doyon, Anke; Canpolat, Nur; Kaplan Bulut, Ipek; Azukaitis, Karolis; Obrycki, Łukasz; Anarat, Ali; et al. (Hypertension, 2023)
BACKGROUND: - - We assessed the effect of blood pressure (BP) control on left ventricular mass index (LVMI) and left ventricular hypertrophy (LVH). - - METHODS: - - Ninety-six patients (64 males) ≥9 months post-kidney transplantation from the 4C-T (Cardiovascular Comorbidity in Children with Chronic Kidney Disease and Transplantation) study were analyzed longitudinally (mean follow-up, 2.6±1.3 years). Cumulative systolic blood pressure (SBP)/diastolic BP exposure was calculated as a time-averaged area under the curve and categorized: ≤50th, 50th to ≤75th, 75th to ≤90th, and >90th percentile (pct). We performed adjusted linear and logistic mixed models for LVMI and LVH, respectively. - - RESULTS: - - At baseline, LVMI was 49.7±12.7g/m2.16 with 64% (n=61) kidney transplantation recipients displaying LVH. Compared with patients with cumulative SBP exposure >90th pct, patients with cumulative SBP of 50th to ≤75th showed a significant LVMI reduction of −5.24g/m2.16 (P=0.007). A similar tendency was seen for cumulative SBP≤50th (β=−3.70 g/m2.16; P=0.067), but patients with cumulative SBP of 75th to ≤90th pct showed no reduction. A post hoc analysis in patients with cumulative SBP≤75th revealed that median SBP exposure was at 57.5th pct. For cumulative diastolic BP, a significant LVMI reduction was seen in all 3 categories ≤90th pct compared with patients >90th pct. Patients with cumulative SBP of ≤50th or 50th to ≤75th pct showed 79% or 83% lower odds of developing LVH, respectively. Patients with cumulative diastolic BP ≤50th showed a tendency of 82% lower odds for LVH (95% CI, 0.03-1.07). - - CONCLUSIONS: - - Stricter BP control led to regression of LVMI and LVH. Our data suggest a BP target below the 60th pct, which needs to be substantiated in a randomized controlled trial.